IDENTIFICATION OF IMPACT FACTORS MINIMUM ESSENTIAL FORCE (MEF) ACHIEVEMENT OF INDONESIAN NAVY ON THE STRATEGIC ENVIRONMENT IN THE NORTH NATUNA MARINE AREA - Arda Widyaksa; Okol Sri Suharyo; Joko Purnomo; April Kukuh Susilo (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
This research focuses on evaluating the current status of the Indonesian Navy's Minimum Essential Force (MEF) in the North Natuna Sea area. This research aims to evaluate the progress of the Indonesian Navy's Minimum Essential Force (MEF) initiative, focusing specifically on its impact within the North Natuna Sea region. Utilizing a qualitative descriptive statistical approach the research using the Delphi Method to support its analysis. The impact of achieving the MEF is dissected into three main criteria: Deterrent Effect, Bargaining Power, and Maritime Security Threat. The research identified 4 sub-factors for both Deterrent Effect and Bargaining Power, and 6 subfactors for Maritime Security Threat, all determined through consensus among expert panelists.